Pharmacological interventions for pediatric irritable bowel syndrome. (2nd January 2022) - Pesce, Marcella; Puoti, Maria Giovanna; Rybak, Anna; Andreozzi, Marta; Bruzzese, Eugenia; Sarnelli, Giovanni; Borrelli, Osvaldo
ABSTRACT: Introduction: Irritable bowel syndrome is a common functional gastrointestinal disorder in children, characterized by recurrent abdominal pain associated with altered bowel habits in terms of both frequency and consistency. According to change in stool consistency it is categorized into 4 subtypes. From the etiological perspective, it is a combination of factors takes part in symptoms' generation, the overall treatment response rate is often unsatisfactory if a multidisciplinary is not pursued. Areas covered: The aim of this manuscript is to summarize the current pharmacotherapy in pediatric irritable bowel syndrome in order to aid clinicians in treating this challenging disorder. Expert opinion: Most evidence involving pediatric populations rely on open label or retrospective studies and/or are not specifically designed for irritable bowel syndrome but tend to generalize their results to mixed populations of children with functional gastrointestinal disorders. A high placebo response rate combined with poor patients' selection could account for the overall weak evidence supporting the use of pharmacological agents in pediatric irritable bowel syndrome. Given the multifaceted nature of the disorder, multidisciplinary approaches combining pharmacotherapy with alternative treatments is highly recommendable.